Clinical and dermoscopic characteristics of Merkel cell carcinoma. (13th August 2013) - Jalilian, C.; Chamberlain, A.J.; Haskett, M.; Rosendahl, C.; Goh, M.; Beck, H.; Keir, J.; Varghese, P.; Mar, A.; Hosking, S.; Hussain, I.; Rich, M.; et al.
Abstract : What's already known about this topic? Two separate studies on the dermoscopic features of Merkel cell carcinoma (MCC) suggest a high prevalence of milky pink areas but show conflicting results on the frequency of linear irregular vessels. What does this study add? We present the largest study of the dermoscopic features of MCC with each case scored independently by three dermoscopists against a set of criteria. We demonstrate a high frequency of several dermoscopic features in MCC. The combination of both sharply focused and poorly focused vessels in the one dermoscopic field is a useful diagnostic feature. Shiny white areas in MCC were observed with both polarized and nonpolarized dermoscopy. Summary: Background: Merkel cell carcinoma (MCC) is an aggressive cutaneous malignancy with a high mortality rate. Diagnosis is often delayed. Objectives: To characterize the dermoscopic features of MCC. Methods: Clinical and dermoscopic images of 12 biopsy‐proven MCCs were analysed in a retrospective manner, with existing dermoscopic criteria being scored independently by three dermatologists. Results: The four most frequent clinical features were cherry red colour, shiny surface, sharp circumscription and nodular morphology. Significant dermoscopic features included linear irregular and polymorphous vessels, poorly focused vessels, milky pink areas, white areas, structureless areas and architectural disorder. Pigmented structures were absent from all lesions. Conclusions: The dermoscopic features described herein help the clinician to distinguish MCC from other benign and malignant red nodules. Increasing recognition of the presenting features will facilitate earlier diagnosis of MCC and reduced mortality.